2016
DOI: 10.1039/c5ra24620b
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of CNT/AgI with enhanced photocatalytic degradation and antibacterial ability

Abstract: Introducing small amount CNT not only reduced the size of the AgI, but also improved the electron–hole separation efficiency and enhanced the photodegradation ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…With increasing CNT concentration, although the resistivity increased slightly from 2.69 to 6.86 μΩ·cm because of the increasing contact resistance between the CNTs and Ag NPs, the photonic energy required for sintering the composite film decreased. This indicates that the IPL photonic-sintering efficiency was enhanced by the unique optical properties of CNTs, that is, their large light absorption and low reflectance in the entire region from far-UV (200 nm) to far-IR (200 μm). , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With increasing CNT concentration, although the resistivity increased slightly from 2.69 to 6.86 μΩ·cm because of the increasing contact resistance between the CNTs and Ag NPs, the photonic energy required for sintering the composite film decreased. This indicates that the IPL photonic-sintering efficiency was enhanced by the unique optical properties of CNTs, that is, their large light absorption and low reflectance in the entire region from far-UV (200 nm) to far-IR (200 μm). , …”
Section: Resultsmentioning
confidence: 99%
“…By investigating the electrical and mechanical properties of the composite electrodes with respect to the CNT concentration, we confirmed that addition of CNTs over 1.8 wt % contributed to the maintenance of continuous electron pathways, which served as bridges connecting the cracked Ag conductive film resulting from mechanical deformation. In addition to this mechanical enhancement, the CNTs improved the photonic sintering efficiency of the CNT/Ag NP composite film during IPL irradiation, boosting the optical absorbance because of their low reflectance and high absorbance over a broad wavelength range. , After selective IPL exposure with a photomask, the IPL-irradiated CNT/Ag composite could not be easily wiped out, because of the strong adhesion caused by interfusion between the underlying polymer substrate and the composite film. In contrast, the nonirradiated region was readily removed from the substrate, enabling patterning of the composite electrode.…”
Section: Introductionmentioning
confidence: 99%
“…35 Alternatively, the h + in the VB of the Bi 2 Se 3 NPs are taken by OH À derived from the aqueous solution and form $OH radicals in the mixed solution. These radicals, O 2 À and $OH, act as oxidizing agents and react with both dye molecules and decompose them into CO 2 , H 2 O, and other small molecules, [42][43][44][45] avoiding the recombination of h + and e À during the photocatalytic process. The complete degradation process of MB and RhB in the presence of Bi 2 Se 3 NPs/PEI as a photocatalyst may be explained with the help of the following equations: In addition to the photocatalytic activity, the stability of photocatalysts is also very important for practical applications.…”
Section: Photocatalytic Degradation Of Mb and Rhbmentioning
confidence: 99%
“…22 24 and CNT/AgI. 25 However, most of these photocatalysts require UV light/visible light to be activated. Therefore the development of photocatalytic agents that can be activated by NIR light which has high occupation of the solar spectrum is more desirable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation